2019
DOI: 10.1177/1363460719842135
|View full text |Cite
|
Sign up to set email alerts
|

‘You're not sure that you are gay yet’: The perpetuation of the ‘phase’ in the lives of young disabled LGBT + people

Abstract: Contemporary discourse on sexuality presents a picture of fluidity and malleability, with research continuing to frame sexuality as negotiable, within certain parameters and social structures. Such investigation is fraught with difficulties, due in part to the fact that as one explores how identity shifts, language terms such as ‘phase’ emerge conjuring images of a definitive path towards an end-goal, as young people battle through a period of confusion and emerge at their true or authentic identity. Seeing se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 23 publications
0
19
0
2
Order By: Relevance
“…Corker (2001) argued that it was really important to explore young lives because they are periods of exploration and getting to know oneself. Similarly, Toft et al (2019b) have reported how for disabled young people periods of sexuality and gender exploration are often viewed as a 'phase' and although it is a period of exploration, this study illustrated that this does not mean that there has to be a specific end-goal. It is just the period in which young people begin to question and understand their own identityand thus worthy of study in its own right.…”
Section: Disability and Sexualitymentioning
confidence: 67%
See 1 more Smart Citation
“…Corker (2001) argued that it was really important to explore young lives because they are periods of exploration and getting to know oneself. Similarly, Toft et al (2019b) have reported how for disabled young people periods of sexuality and gender exploration are often viewed as a 'phase' and although it is a period of exploration, this study illustrated that this does not mean that there has to be a specific end-goal. It is just the period in which young people begin to question and understand their own identityand thus worthy of study in its own right.…”
Section: Disability and Sexualitymentioning
confidence: 67%
“…These studies are often small qualitative studies pro-viding a rich depth of experiences, often shedding light on societal, structural and cultural factors that impact on the lives of LGBT+ disabled young people (e.g., Dinwoodie et al, 2016;Juvva et al, 2020, Michaels andGorman, 2020). These studies have offered an insight into the worlds of this group of young people, but rarely have researchers reported the barriers and facilitators that have enabled them to connect with this groupa group whose authentic lives are often hidden, who are often prevented from making their own choices, decisions and/or being able to express themselves, their views and experiences (Toft et al, 2019b).…”
Section: Young Disabled Lgbt+ Studiesmentioning
confidence: 99%
“…As previously noted I take inspiration from the work of Orne (2011) and his call to explore coming out as a strategic identity management tool which can help to unpick identities and intersections. In order to do this, I use what I have previously called intersectional story-telling, a form of narrative driven intersectional analysis (Toft et al 2019b). I propose that exploring experiences and events, whilst always foregrounding the voices of the participants, is an effective starting point for understanding individual's relation to society and the self.…”
Section: Theoretical Framingmentioning
confidence: 99%
“…One of the prevailing misconceptions young disabled LGBT+ people face is that their sexuality or gender identity can be attributed to going through a phase or being in a position of temporariness (Toft et al 2019b). Taking a metaphor from Plummer (1995) we are seen to be navigating a sea of questions and uncertainties before eventually arriving home.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation